Epigenetic changes in patients with post-acute COVID-19 symptoms (PACS) and long-COVID: A systematic review - Madhura Shekhar Patil; Emma Richter; Lara Fanning; Jolien Hendrix; Arne Wyns; Laura Barrero Santiago; Jo Nijs; Lode Godderis; Andrea Polli (Expert Reviews in Molecular Medicine)
Abstract Background Up to 30% of people infected with SARS-CoV-2 report disabling symptoms 2 years after the infection. Over 100 persistent symptoms have been associated with Post-Acute COVID-19 Symptoms (PACS) and/or long-COVID, showing a significant clinical heterogeneity. To develop effective, patient-targeted treatment, a better understanding of underlying mechanisms is needed. Epigenetics has helped elucidating the pathophysiology of several health conditions and it might help unravelling inter-individual differences in patients with PACS and long-COVID. As accumulating research is exploring epigenetic mechanisms in PACS and long-COVID, we systematically summarized the available literature on the topic.